CONTRASTIVE ANALYSIS ON EASTERN-WESTERN PRONOUNS - Khristianto Khristianto (University of Muhammadiyah Purwokerto, 2011)
Contrastive analysis in this article is applied on translation involving three different languages, i.e. Indonesian and Javanese (Eastern languages) and English (Western language). Analysis on the data results in the fact that Western has more complete realization of experienced entity, as proved in the complete pronoun for all (first, second, third and also human or non-human). The Eastern doesn’t realize the perceived existence in a complete pronoun. Bahasa is lack of third person for non-human, and Javanese has no practical third person either for human or non-human, as found in the translation data. Eastern is concerned more on the realization of different social and interpersonal relation between speaker, interlocutor and the third person mentioned in the interaction. Thus, Eastern is rich with variation in addressing another among of which is formulated in the H and S for “I”, “you” and “he”.